Establishing Diagnostic Reference Levels in Digital Mammography from Eight Mammography Units Using over 30,000 Images - Mediji-Arifi, Mirjeta; Ristova, Mimoza (MDPI AG, 2025)
Introduction: Diagnostic reference levels (DRLs) in digital mammography were determined from 31,040 digital mammography images acquired from diagnostic and screening examination data from eight state-managed mammography centers/units in the Republic of North Macedonia (RM). The main objective is to establish a diagnostic reference level for mammography examinations at different ranges of breast thickness. Materials and methods: Approximately 30,000 mammography images were used to evaluate mean glandular dose (MGD) and compressed breast thickness (CBT) for each projection, craniocaudal (CC) and mediolateral oblique (MLO). The stratified DRL was derived by calculating the 75th percentile of the MGD across all the samples at various CBT ranges for both projections. Results and Discussion: The overall median MGDs, minimum, and maximum were calculated to be 1.15 mGy, 0.1 mGy, and 9.93 mGy, respectively. As the CBT increased from 7 to 120 mm, the 75th percentile of the MGD increased from 0.94 mGy to 3.67 mGy for CC, and from 0.44 mGy to 4.91 mGy for MLO projections. Conclusions: The study established local DRLs for the digital mammography systems at the 75th percentile, which compared well with the values reported for other countries/regions. The DRL defined per CC and MLO image view for a specific CBT indicated that at least one mammography facility needs optimization.
Keywords: digital mammography; mean glandular dose (MGD); compressed breast thickness; diagnostic reference level (DRL); radiation exposure